West African Economic and Monetary Union : Financial Sector Assessment Program-Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The Financial Sector Assessment Program (FSAP) was conducted amid an economic rebound two years into the COVID-19 pandemic that had a limited impact on the financial sector. Several member states have experienced political instability, with coups in Burkina Faso and Mali leading to economic sanctions for the latter, and an attempted coup in Guinea-Bissau. Yet, short of further political deterioration, economic recovery is expected to persist. The last FSAP was conducted in 2008.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; International Agreements and Observance; International Organizations; Monetary Policy